1989
DOI: 10.1016/s0022-5347(17)41343-7
|View full text |Cite
|
Sign up to set email alerts
|

Class I and Class II HLA Antigen Expression by Transitional Cell Carcinoma of the Bladder: Correlation with T-Cell Infiltration and BCG Treatment

Abstract: HLA class I and II glycoproteins from transitional cell carcinoma (TCC) and from perineoplastic and healthy vesical mucosa were characterized together with infiltrating cells by means of immunochemistry using specific monoclonal antibodies on frozen sections obtained during resection or radical cystectomy. Specimens were taken from 11 patients with TCC and five with healthy bladder mucosa. Four patients with TCC and four with healthy mucosa had been previously treated with a course of intravesical bacillus Cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…22 Only scant data on the relation between HLA-II ex pression and bladder cancer have been published and al though HLA-II expression was found in bladder cancer and correlated with B C G therapy23,24 and was induced by cyto kines,25 no correlation has been found between HLA-II ex pression and tumor aggressiveness. 24,26 A consistent value of the epidermal growth factor receptor (EGF-R) in T C C has been recently reported.9-27 Normally, EGF-R is found only on the basal layer of epithelial cells. In bladder tumors the urinary concentration of E G F can be decreased, but EGF-R expression in tumors is higher than in normal urothelium.…”
Section: Discussionmentioning
confidence: 62%
“…22 Only scant data on the relation between HLA-II ex pression and bladder cancer have been published and al though HLA-II expression was found in bladder cancer and correlated with B C G therapy23,24 and was induced by cyto kines,25 no correlation has been found between HLA-II ex pression and tumor aggressiveness. 24,26 A consistent value of the epidermal growth factor receptor (EGF-R) in T C C has been recently reported.9-27 Normally, EGF-R is found only on the basal layer of epithelial cells. In bladder tumors the urinary concentration of E G F can be decreased, but EGF-R expression in tumors is higher than in normal urothelium.…”
Section: Discussionmentioning
confidence: 62%
“…MHC Class II antigens serve as restriction elements for cells that present antigens to CD4 + helper T cells, and it has been reported that intravesical BCG treatment induces the expression of MHC Class II on normal urothelium and bladder tumor cells in patients. [8][9][10][11][12] The CD1 family are class I-like antigen presentation molecules, and it is reported that glycolipids of mycobacteria, including BCG, serve as their ligands and activate NKT cells and may have an important role in the antitumor effect. 13 Considered most important for T cell activation as a major ligand of CD28 is CD80 (B7-1), which is a major costimulatory molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic bladder‐wall infiltration of immune cells, such as T lymphocytes (predominantly CD4 + T cells) and activated macrophages has been reported 6 . BCG is also known to induce MHC class II molecules 7 and intracellular adhesion molecule (ICAM)‐1 molecule expression 8 in normal and tumor urothelial cells. In an animal model, Ratliff et al 9 .…”
Section: Discussionmentioning
confidence: 99%